Myślą i piórem : 7. rocznica powstania "Naszego Dziennika" / Adam Lepa [et al.]. - Lepa, Adam (1939-2022); Bajda, Jerzy (1928-2012); Bartnik, Czesław Stanisław (1929-2020) (SPES, 2005)
Audycje i pieśni.